How much community engangement of patient stakeholders has there been on the National Health Insurace ? A bioethic enquiry - Tandwa, Lizeka (My University, 2018)
Community engagement in health refers to the collaborative effort of citizens in a community to organize and participate in health promotion, research and policy development. Community engagement encompasses the participation of patients at micro, meso and macro levels. The National Health Insurance (NHI) is a South African health legislation that is under development which aims to ensure universal health coverage. Community involvement is a constitutional requirement and the policy makers of the NHI have a duty to involve the community and specifically; patients in the decision-making and implementation of the policy
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg
Keywords: Bioethical; community engagement; patient; National Health Insurance